An investigation of influential factors in adopting the cloud computing in Saudi Arabia: an application of technology acceptance model - ALresheedi, Shayem; Lu, Songfeng; Yaqub. Maolood, Ismail; Abdulwaha, Abdulaziz; Mahmut Incee, Fatanid (International Journal of Engineering and Technology, 2018)
Cloud computing is an emerging concept in the technological sphere. Its development enables many applications to avail information online and on demand. It is becoming an essential element for businesses due to its ability to dimin-ish the costs of IT infrastructure and is being adopted in Saudi Arabia. However, there exist many factors that affect its adoption. Several researchers in the field have ignored the study of the TAM model for identifying the relevant fac-tors and their impact for adopting of cloud computing.Â Â Â Â